2009
DOI: 10.1007/s11269-009-9505-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Crop Coefficient and Evapotranspiration of Wheat (Triticum aestivum) in an Irrigation Command Using Remote Sensing and GIS

Abstract: Remote sensing and Geographical Information System (GIS) techniques were used to estimate actual crop evapotranspiration of wheat crop grown in Tarafeni South Main Canal (TSMC) irrigation command of West Bengal State in India. The area under wheat crop was clipped from landuse/land cover map generated from Indian Remote Sensing Satellite P6 (IRS P6) image of January, 2004 for winter season 2003-04. The IRS P6 image and four wide field sensor (WiFS) images for different months of winter season were used to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 9 publications
1
37
0
Order By: Relevance
“…These two seasons were characterized because in the initial stage crop needs smaller water requirements, whereas in the mid-season crop needs higher water requirements, as we can see in the next section. The ET c maps created in this study are in agreement with other researchers; for example, in [2,4,58,59], they generated ET c maps using c derived from remote sensing-based vegetation indices. Other researchers reported that c derived from canopy reflectance based vegetation index had the potential to estimate crop evapotranspiration at regional and field scales, for example, in [17,18,29,55,60,61].…”
Section: 3supporting
confidence: 89%
See 3 more Smart Citations
“…These two seasons were characterized because in the initial stage crop needs smaller water requirements, whereas in the mid-season crop needs higher water requirements, as we can see in the next section. The ET c maps created in this study are in agreement with other researchers; for example, in [2,4,58,59], they generated ET c maps using c derived from remote sensing-based vegetation indices. Other researchers reported that c derived from canopy reflectance based vegetation index had the potential to estimate crop evapotranspiration at regional and field scales, for example, in [17,18,29,55,60,61].…”
Section: 3supporting
confidence: 89%
“…High values of NDVI are related to healthy and dense vegetation, which presents high reflectance values in the NIR waveband and low reflectance values in the red waveband [17]. Crop coefficients generated from VIs determine ET c better than a tabulated c because it represents the actual crop growth conditions and capture the spatial variability among different fields [2,18,19].…”
Section: Advances In Meteorologymentioning
confidence: 99%
See 2 more Smart Citations
“…Several research studies have successfully developed ET prediction models using VIs for different vegetation covers [19] including shrub lands [20,21], riparian sites [22][23][24][25], and over regional scales with a variety of land covers/land uses of grasslands to forests [26,27]. NDVI, the most widely used VI, quantifies the vegetation's photosynthetic response to red radiation absorption and near infrared reflectance [28][29][30][31][32][33]. For most satellites, NDVI is computed from Equation 1:…”
Section: Study Areamentioning
confidence: 99%